GIANT SUBMUCOSAL LEIOMYOMA PRESENTING WITH A VERY LARGE ABDOMINOPELVIC SOFT TISSUE MASS WEIGHING 5 KG - Dr Sukesh Gowda KS; Dr Kiran Prabhakar Rebello (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
We report a rare case of a giant submucosal leiomyoma weighing 5 kg and measuring 20 x 15 cm, presenting with abdominal pain, lower abdominal fullness, menorrhagia, and right-sided hydronephrosis. Despite significant thrombocytopenia, the patient successfully underwent total abdominal hysterectomy with right salpingo-oophorectomy after preoperative optimization. Histopathology confirmed a benign submucosal leiomyoma. This case highlights the importance of multidisciplinary management in complex presentations of uterine fibroids.